Effect on the temperature behavior of glass fiber reinforced polymer (GFRP) in various application - A review - Itam Z.; Ishak Z.A.M.; Yusof Z.M.; Salwi N.; Zainoodin M. (American Institute of Physics Inc., 2023)
Glass Fibre-Reinforced Polymer (GFRP) composite are one of the most common FRP materials. GFRP properties mostly depend on the characteristics of its constituent materials, fiber orientation, and content, also the interaction between fiber and matrix. In a transmission line, GFRP crossarm was introduced and used as a protection material to distribution and transmission system due to high dielectric strength and non-conductivity. This paper is a review of past study and to achieve an objective which is in order to investigate the GFRP based on its temperature behavior performance in the various application. 2018 Author(s).